2020
DOI: 10.1017/s1479262120000313
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of QTL-allele system for drought tolerance at seedling stage and optimal genotype design using multi-locus multi-allele genome-wide association analysis in a half-sib population of soybean (Glycine max (L.) Merr.)

Abstract: Characterizing the whole genetic architecture of drought tolerance (DT) is a persistent challenge for the breeders. Here we developed a half-sib population comprising of 404 lines of two recombinant inbred line (RIL) populations with M8206 as the joint parent (M8206 × TongShan and ZhengYang × M8206) and tested for its DT under sand culture. The population was sequenced using restriction-site-associated DNA sequencing filtered with minor allele frequency ≥0.01; 55,936 single nucleotide polymorphisms (SNPs) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…We found that RTM-GWAS was effective in identifying QTLs in a bi-parental RILs population and identified more QTLs that overlapped with previous Meta-QTLs than that in linkage mapping. Similarly, RTM-GWAS showed a more effective QTL detection rate in soybean bi-parental RILs populations, and lower false positives compared to linkage mapping or traditional GWAS (Pan et al 2018 ; Khan et al 2020 ; Chang et al 2021 ; Zou et al 2021 ). Our result proved that integration of linkage mapping and RTM-GWAS can highlight important QTLs, such as qST-5.1 and qST-6.1 in this study.…”
Section: Discussionmentioning
confidence: 97%
“…We found that RTM-GWAS was effective in identifying QTLs in a bi-parental RILs population and identified more QTLs that overlapped with previous Meta-QTLs than that in linkage mapping. Similarly, RTM-GWAS showed a more effective QTL detection rate in soybean bi-parental RILs populations, and lower false positives compared to linkage mapping or traditional GWAS (Pan et al 2018 ; Khan et al 2020 ; Chang et al 2021 ; Zou et al 2021 ). Our result proved that integration of linkage mapping and RTM-GWAS can highlight important QTLs, such as qST-5.1 and qST-6.1 in this study.…”
Section: Discussionmentioning
confidence: 97%